Analsis Kemampuan Peserta Didik pada Sumatif Akhir Semester (SAS) Menggunakan Pendekatan Item Response Theory (IRT) Berbantuan Modular Object-Oriented Dynamic Learning Environment (MOODLE) - Prabaningtias, Dea Arsi; Arman, Daly (Pendidikan Teknologi Informasi Universitas Bumigora, 2023)
This article aims to determine the quality of instruments and the ability of end-of-semester summative learners in science subjects’ grade 7 at MTsN 1 Ketapang using the Item Response Theory (IRT) approach assisted by Modular Object-Oriented Dynamic Learning Environment (MOODLE). Respondents involved in this study were 287 learners with 25 question items. The application used for item response theory is Software Quest. The results of the analysis using Quest Software show that the reliability reliability is very high, validity is good, and the level of difficulty is good. Based on the analysis using item response theory, teachers can know the quality of the assessment of the questions developed and the ability of students. The use of analysis with item response theory is recommended to be used by every teacher to help teachers in knowing the quality of the assessment questions developed and the ability of students. every teacher so that it can help teachers in knowing the quality of the assessment instrument and the ability of student.